Sludge or serpent? Unmasking hepatobiliary ascariasis in a young adult female - Quadri, Ahmed Alam; Jawad, Anaya; Khan, Gazala; Ali, Mohammed Abdul Muhaimin; Quadri, Khadijah Amatul Noor; Ali, Zabreen Fatima Sikunder; Abidi, Syed Ali Raza; Quadri, Afreen; Rasheed, Faizan (International Journal of Research in Medical Sciences, 2025)
Hepatobiliary ascariasis (HBA) is an uncommon but significant cause of biliary obstruction, particularly in regions where Ascaris lumbricoides is endemic. We report a case involving a 21-year-old female who presented with severe epigastric pain and vomiting. Initial evaluation indicated biliary sludge and possible pancreatitis, but her symptoms worsened despite conservative management. Repeat ultrasonography revealed a coiled echogenic structure in the right hepatic and common bile ducts, raising suspicion for parasitic infestation. Magnetic resonance cholangiopancreatography (MRCP) confirmed a tubular filling defect, and endoscopic retrograde cholangiopancreatography (ERCP) enabled extraction of a live Ascaris worm. The patient was treated with albendazole and scheduled for elective cholecystectomy due to persistent gallbladder sludge. This case highlights the importance of considering parasitic infections in the differential diagnosis of biliary symptoms in endemic regions. Early imaging and prompt endoscopic intervention are crucial to prevent complications. Preventive strategies, including improved sanitation, health education, and regular deworming, are essential to reduce the burden and recurrence of ascariasis.